Numerical Simulation of Grounding Characteristics and Temperature Field of Mine Tires under Multiple Working Conditions - Jinquan Guo; Peng Ding; Jianhong Gao; Zhenhua Huang; Qiyan Guo; Xiaoxiang Yang (Advances in Polymer Technology, 2022)
Mine tires are an essential and expensive component of heavy mining machinery. This study explored the grounding characteristics and temperature field distribution of mining tires during driving as well as the relationships between the maximum temperature and tire inflation pressure, load, and speed. Two-dimensional and three-dimensional finite element models of mine tires were established. Steady-state rolling simulation analysis was conducted based on inflation and static load simulations. Temperature field simulation analysis was conducted with the tire section as a research object. The accuracy of the finite element model was verified. Analysis results demonstrated that the grounding contact area decreased with an increase in charging pressure and increased with an increase in load. With an increase in inflation pressure, the maximum normal grounding stress increased in the middle part of the tread and decreased near the shoulder. The maximum normal grounding stress continuously deviated in the shoulder direction with an increase in load. Temperature field analysis indicated that the tire had the maximum temperature at the binder position, where the first belt layer was connected to the second belt layer, which corresponds to the maximum stress position in the steady-state rolling simulations. Tire temperature increased with driving speed. The maximum temperature increased with an increase in tire deflection, whereas the deflection decreased with an increase in inflation pressure and increased with an increase in load. Speed had the greatest influence on the maximum temperature, followed by load, with inflation pressure having the smallest influence. The results of this research can be used to improve the service life of mine tires to improve productivity and reduce costs.